Going virtual: a report from the sixth Young Microbiologists Symposium on 'Microbe Signalling, Organisation and Pathogenesis'. Issue 3 (2nd March 2021) - An, Shi-qi; Lopes, Bruno Silvester; Connolly, James P. R.; Sharp, Connor; Nguyen, Thi Kim Loan; Kirkpatrick, Clare Louise
Abstract : The sixth Young Microbiologists Symposium on 'Microbe Signalling, Organisation and Pathogenesis' was scheduled to be held at the University of Southampton, UK, in late August 2020. However, due to the health and safety guidelines and travel restrictions as a response to the COVID-19 pandemic, the symposium was transitioned to a virtual format, a change embraced enthusiastically as the meeting attracted over 200 microbiologists from 40 countries. The event allowed junior scientists to present their work to a broad audience and was supported by the European Molecular Biology Organization, the Federation of European Microbiological Societies, the Society of Applied Microbiology, the Biochemical Society, the Microbiology Society and the National Biofilms Innovation Centre. Sessions covered recent advances in all areas of microbiology including: Secretion and transport across membranes, Gene regulation and signalling, Host–microbe interactions, and Microbial communities and biofilm formation. This report focuses on several of the highlights and exciting developments communicated during the talks and poster presentations.